Pulmonary artery aneurysm in an adult patient with idiopathic dilatation of the pulmonary artery - Betkier-Lipińska, Katarzyna; Suwalski, Grzegorz; Czarkowski, Sebastian; Hendzel, Piotr; Cwetsch, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Idiopathic dilatation of the pulmonary artery (IDPA) is a rare congenital heart disease. It has been described for almost one hundred years, and numerous definitions have been proposed. The IDPA diagnostic criteria have not been updated for years. Secondary to primary disease, pulmonary artery aneurism was recognised as a lethal defect; however, long-term follow-up of patients with IDPA has not been well researched. Thus, indications to medical or surgical treatment are not evidence based. Here, we present a rare case of a 54-year-old patient with IDPA, who remained under observation for 36 years without surgical intervention.